Effects of industrial wastewater on water and sediment qualities and effectiveness of bioremediation methods of industrial wastewater treatment, Gebeng, Pahang, Malaysia - Md Abdus, Sobahan (2015)
Gebeng is a very important industrial estate of Pahang, Malaysia. A study was conducted in Gebeng industrial area in order to obtain the current status of industrial wastewater, surface water and sediments. Results of industrial wastewater and surface water were compared to Malaysian and different standards limits. Moreover, the industrial wastewater and surface water classification and contamination intensity were calculated. Sediment quality guidelines were used to compare the results of sediments. Some of water quality parameters such as BOD, COD, TSS, Pb, Cd, Cr and Hg were higher compared to standard limits in studied wastewater. BOD, COD, ammoniacal nitrogen, total nitrogen, total phosphorous, nitrate, phosphate, As, Hg, Co, Pb, Ni, Cr, Cd and Cu were higher in surface water compared to standard threshold. For sediments, Co, Hg, As, Pb and Cu concentrations were higher than those of permissible levels. In addition, wastewater treatments were done by bio-remediation methods. It was performed first by Pseudomonas aeruginosa and secondly by Vetiver grass, Cattails and Water hyacinth. From the treatments of Pseudomonas aeruginosa, the expected pollutants removal efficiency was found. Because of lower pollutants tolerant features vetiver grass and water hyacinth did not survive in 100 % wastewater while cattails were adapted to 100 % wastewater due higher contaminants tolerant characteristics. The 75 % wastewater with N-P-K mixed fertilizer treatment was found as the best treatments among vetiver grass and water hyacinth treatments. In case of cattails, 100 % wastewater with mixed fertilizer treatment showed the best performance. Statistical software (SPSS) was used to compute data and results. Least significance difference, first order kinetics, correlation analysis, principal component analysis, pollution load index, contamination factors, geo accumulation index and surface water enrichment factors were used to test the significance, validity of data, groupings of parameters and interpretation. In this study, a novel two steps technique was used which proven to give higher efficiency compared to direct treatments with plants. From this study, it could be concluded that the study area is moderately contaminated by industrial wastewater. Furthermore, the surface waters are classified as polluted (DOE-WQI) and sediments are very strongly and strongly polluted by Co and Hg respectively while Pb, Cd and As are found unpolluted to moderately polluted. So, recycling of wastewater, wastewater treatments by bioremediation techniques, close monitoring and supervision in every industry have to be introduced.